IMPLIKASI BLACKLIST BAGI PIHAK DEBITUR LAMA YANG TIDAK BERSALAH AKIBAT WANPRESTASI PIHAK DEBITUR BARU (STUDI KASUS: OVERCREDIT SEPEDA MOTOR) - Dinira , Amanda; Auni, Amira; Febriana , Annisa Nur; Nur Sabilla , Cica; Aulia , Cindy; Lestari Ramadhani , Mustika; Zanna, Rika Tul; Nur Iqbal, Muhammad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study analyzes motorcycle overcredit cases involving old debtors. new debtors, and BAF as intermediaries. The old debtor overcredits the motorcycle with the new debtor through BAF, with the initial down payment made by the new debtor to the old debtor. However, after the overcredit deal was agreed and witnessed by BAF, the debtor did not make the next payment at all. BAF then requests payment from the old debtor, who then shows evidence that the overcredit has been carried out legally. This study aims to find out the legal responsibilities of the old debtor and the new debtor in this case, as well as the legal implications for the old debtor who is blacklisted due to the actions of the new debtor. This study uses a qualitative research method with a case study approach. This research method was chosen because this research aims to understand in depth about payment responsibilities in motor overcredit transactions. The results of the study show that the old debtor has fulfilled its obligations in overcredit, but is still affected by the law because the new debtor does not make the next payment. This research is expected to contribute to the understanding of the law of overcredit and protection for the innocent.